Measuring Metacognitive Awareness of Reading Strategies of Higher Level Learners - Khatri, Krishna Kumar (Rupantaran: A Multidisciplinary Journal, 2021)
The metacognitive awareness of reading strategies among higher level learners has been widely acknowledged for successful reading comprehension. However, literature shows a little empirical research in this area in Nepalese context. This paper attempts to measure the metacognitive awareness of reading strategies of higher level learners of Nepal. As a quantitative study, cross-sectional survey design was used to obtain the primary data from 142 higher level learners pursuing MPhil degree from different universities of Nepal through questionnaire. The metacognitvie awareness of reading strategies of the learners was measured in univariate analysis and difference of their awareness in terms of independent variables was assessed in bivariate analysis using t-test. The study revealed that higher level learners had metacognitive awareness of reading strategies at different levels. Among the three groups of strategies, cognitive strategies were found most frequently used by the learners and supportive strategies were found least frequent to them. The independent variables i.e. sex and subject of specialization did not affect in the learners’ metacognitive awareness of reading strategies. The differences were not seen statistically significant. This implies that teacher can use and instruct the learners with similar type of reading strategies irrespective of gender and group of subjects.